Adelmidrol: A New Promising Antioxidant and Anti-Inflammatory Therapeutic Tool in Pulmonary Fibrosis - Fusco, Roberta (Antioxidants (Basel), 2020)
Background: Chronic pulmonary diseases are characterized by airway remodeling due to complex multicellular responses and the production of free oxygen radicals. They lead to a progressive decline of pulmonary functions. Adelmidrol is an analogue of palmitoylethanolamide (PEA), which is a well-known anti-inflammatory and anti-oxidant compound. In this study, we investigated the efficacy of adelmidrol (10 mg/Kg) for bleomycin-induced pulmonary fibrosis in mice. Methods: Bleomycin intratracheal administration was performed on the first day and for the following twenty-one days, mice were treated with adelmidrol (10 mg/Kg). Results: The survival rate and body weight gain were recorded daily. At the end of the experiment, adelmidrol-administered animals showed reduced airway infiltration by inflammatory cells, Myeloperoxidase (MPO) activity, and pro-inflammatory cytokine overexpression (IL,6 IL-1β, TNF-α, and TGF-1β). Moreover, adelmidrol treatment was able to manage the significant incapacity of antioxidants and elevation of the oxidant burden, as shown by the MDA, SOD, and GSH levels and decreased nitric oxide production. It was also able to significantly modulate the JAK2/STAT3 and IκBα/NF-kB pathway. Histologic examination of the lung tissues showed reduced sample injury, mast cell degranulation, chymase activity, and collagen deposition. Conclusions: In sum, our results propose adelmidrol as a therapeutic approach in the treatment of pulmonary fibrosis.